Right ventricular filling in dilated cardiomyopathy. - Fujimoto, S. (1995)
PURPOSE--To assess right ventricular filling in dilated cardiomyopathy. PATIENTS--32 patients with dilated cardiomyopathy and 24 healthy controls. METHODS--Stroke distances were measured by pulsed Doppler echocardiography at left ventricular outflow and left and right ventricular inflow. The inflow tract dimensions of both ventricles and the outflow tract dimension of the left ventricle were measured from two dimensional images. Right and left sided atrioventricular (AV) ring excursions were measured by M mode echocardiography at the tricuspid and mitral rings. Stroke volume was derived as stroke distance multiplied by left ventricular outflow tract area. Total stroke distances were calculated as the sum of AV valve Doppler stroke distances and ring excursion. The effective orifice areas of the two AV valves were thus defined as stroke volumes divided by total stroke distance. RESULTS--Total tricuspid stroke distance was normally less than mitral (6.0 (1.7) v 7.6 (1.7) cm, P < 0.05), implying that effective orifice area of the tricuspid valve was consistently greater (6.6 (1.6) v 4.5 (0.8) cm2, P < 0.01). Total tricuspid ring excursion was normally more than mitral (2.30 (0.30) v 1.62 (0.22) cm, P < 0.01). Total tricuspid stroke distance in dilated cardiomyopathy was also less than mitral (7.8 (2.4) v 9.7 (2.8) cm, P < 0.05). Tricuspid stroke distance was significantly increased in patients with dilated cardiomyopathy compared with that in healthy controls (P < 0.05 v controls), though stroke volume was much smaller (26 (10) v 63 (11) ml, P < 0.01) so that tricuspid effective orifice area was reduced to less than half normal (2.7 (1.2) cm2, P < 0.01). Total tricuspid ring long axis excursion was more than mitral (1.37 (0.6) v 0.74 (0.21) cm, P < 0.01). Right ventricular end diastolic inflow dimension was increased compared with that in healthy controls (3.9 (0.7) v 2.8 (0.5) cm, P < 0.01), correlating inversely with tricuspid effective orifice area (r = -0.71, P < 0.01). Total tricuspid ring excursion was bimodally distributed as a low amplitude group (less than 1.6 cm, n = 23) and a high amplitude group (more than 1.6 cm, n = 9), in which the interval P2 to onset of tricuspid flow was much longer (100 (35) v 50 (14) ms, P < 0.01). CONCLUSIONS--Enlargement of the right ventricular inflow tract in dilated cardiomyopathy, especially to more than 5 cm, is accompanied by a progressive decrease in effective tricuspid orifice area, sometimes to less than 1 cm2 and increased inflow velocities. Right ventricular relaxation was incoordinate in 28% of the patients studied. These disturbances of right ventricular filling are likely to compromise overall cardiac function independently of left ventricular disease.